In situ gamma-ray measurements of marine sediment using Monte Carlo simulation - Androulakaki, E.; Tsabaris, C.; Patiris, D. L.; Eleftheriou, G.; Kokkoris, M.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2012)
This work outlines the progress in developing a new method for in situ radioactivity measurements of marine sediments. The method combines the underwater gamma-ray spectrometer (a system named KATERINA based on a NaI(Tl) detector) with Monte-Carlo calculations using the MCNP5 code. This method aims at allowing for an accurate quantitative determination of activity concentrations in marine sediments (using the in situ system), which can be applied in different areas and for variable sediment structures. As a first step, the MCNP5 code has been successfully applied for the standard 4π geometry in the aquatic environment, reproducing results of the marine efficiency as previously deduced by the GEANT4 code. The experimental set up geometry was introduced in MCNP5 using detailed information for the geometry and the materials. Moreover, a first simulated estimation of the in situ efficiency for sediment measurements is presented for 40K (1460.8 keV). For this purpose a new model was constructed taking into account a typical experimental geometry set-up (with the detector being situated in close contact with the seabed). In order to validate the Monte-Carlo results, activity measurements were also performed in sediment samples collected from Basilica, Cyprus, where the in situ system was deployed. The samples were analysed using a HPGe detector for inter-calibration purposes and the obtained results are discussed.